Interleukin 18 promoter variants (−137G>C and −607C>A) in patients with chronic hepatitis C: association with treatment response - Haas, Stephan; Weiß, Christel; Bugert, Peter; Gundt, Jutta; Witt, Heiko; Singer, Manfred V.; Berg, Thomas; Böcker, Ulrich (Journal of clinical immunology, 2009)
Recently, two functional IL18 promoter variants, −607C>A (rs1946518) and −137G>C (rs187238), were associated with viral clearance in patients with hepatitis C. The present study focused on their relevance for treatment response.